Participation in Decision Making as a Non-Financial Incentive for Enhancing Employee Performance in the Enugu State Civil Service (2010–2019) - Chibuike Chris Umeokafor (ROE: Research of Economics and Business, 2026)
Persistent problems of low motivation and suboptimal productivity continue to affect the Enugu State Civil Service despite the provision of regular monetary incentives. This study examined participation in decision-making as a non-financial incentive for enhancing employee performance in the Enugu State Civil Service between 2010 and 2019. A descriptive research design was adopted. The study population comprised 10,100 civil servants across twenty ministries, from which a simple random sample of 385 employees was selected using Yamane’s (1967) formula. Primary data were collected through structured interviews with key officials and administrators, and were complemented by secondary sources such as journal articles, government reports, and official publications. Instrument reliability and validity were ensured through careful construction and content validation. Data were analyzed using content analysis. The findings revealed that employee participation in decision-making significantly enhances performance by fostering a stronger sense of belonging, ownership, and responsibility among workers. Participatory practices were found to improve motivation, job satisfaction, organizational commitment, creativity, and employees’ willingness to share knowledge and collaboratively solve problems. The study further showed that ministries in Enugu State actively utilize non-financial incentives, including participatory decision-making, recognition, training opportunities, and delegated authority. Importantly, structured participatory mechanisms were found to reduce workplace dissent and resistance to organizational decisions, thereby sustaining productivity. The study concludes that participatory decision-making is a powerful and effective non-financial motivational strategy for improving employee performance in the Enugu State Civil Service.